Uso do Big and Safe Dividends para a formação de carteiras de ações no Brasil : uma análise sob a ótica do dividend investing - Viana, Dêner Matheus da Silva (2022)
The study aimed to investigate the efficiency of Big, Safe Dividends (BSD) as an investment strategy for the formation of winning stock portfolios in the Brazilian stock market. Big Safe Dividends is an indicator developed by Carlson (2010) that allows the creation of a ranking of companies based on 10 financial filters that reflect their fundamentals, as well as their ability to pay large and safe dividends. In this sense, stock portfolios were create based on this asset selection methodology, adapted to the context of the Brazilian stock market. For data collection, were used the Economatica and Thonsom Reuters Eikon databases. Then, portfolios with 10, 15 and 20 assets formed, for greater flexibility in choosing stocks for investment strategy and rebalanced each year between 2010 and 2020. It is, added that the study carried out an analysis on the possible generation of alpha of the formed portfolios. The results show that all the portfolios formed by BSD presented returns superior to the main indices of the Brazilian market (Ibovespa, Corporate Governance Index and IBRx100) except for the dividend index (IDIV), with the portfolio formed by the ranking of 15 assets being the strategy that obtained the highest accumulated return at the end of the analyzed period. In order to assess and explain the abnormal return by the portfolios, this research used the five-factor asset pricing model suggested by de Fama and French (1992, 1993), Cahart (1997) and Amihud (2002). The results found indicate that the “dividends” factor represented by the portfolios formed by BSD (10 and 20 assets) explain the stock returns in Brazil, presenting a positive and significant relationship with the Ibovespa, the main stock index in the Brazilian market. Additionally, the portfolios formed by the ranking of 10, 15 and 20 assets managed to generate alpha at a 1% significance level. The results suggest that it is possible to obtain abnormal returns in Brazil through a strategy based on dividend investing. In this way, the study contributes by presenting an alternative and adequate methodology with the practical reality of an investor, especially the investor of dividend companies, differing from previous research that did not explore such issues. In addition, it reinforces for users of accounting information the use of solid and reliable criteria for selecting stocks to compose portfolios, since they are already empirically tested, and therefore can ensure better performance. In fact, the use of various indicators prevents investors from falling into traps, such as non-recurring dividends or high dividend yields caused by a fall in the share price, that is, due to the loss of fundamentals. Therefore, participants in the stock market in general will be able to use the results to base their investment theses and make the best decisions.